Penatalaksanaan Fisioterapi Post Craniotomy Intracranial Hemorrhage Di RSU PKU Muhammadiyah Yogyakarta - Suryawan, Dewa Made Bayu; , Totok Budi Santoso, S.Fis, MPH (2015)
Background: Post craniotomy postoperative intracranial hemorrhage a head because of bleeding in the brain due to the rupture of blood vessels in the brain. This condition can lead to problems of physiotherapy due to bed rest, such as: (1) limited range of motion, and the potential occurrence of atrophy, contractures and spasticity (2) the potential occurrence of decubitus ulcers (3) excessive production of sputum or phlegm and atelectasis. Result : To study about physiotherapy management in bed rest, to prevent a limited range of motion, prevent decubitus ulcers and clearing the airways with modalities relaxed passive movement,chest physiotherapy and positioning. Results: After treatment for 6 times the result of motion assessment at T1: full ROM into T6: full ROM, on inspection of decubitus ulcers T1: no decubitus ulcers become T6: no decubitus ulcers, sputum layout T1: area of the trachea to bronchi (the most dominant position), all side lobes become T6: trochea area until the bronchi (the most dominant position), all side lobes remain evenly by the number of 200 ml / day. Conclusion: relaxed passive movement can prevent a decrease in range of motion due to bed rest, positioning can prevent decubitus ulcers due to bed rest and chest physiotherapy can prevent the build up of sputum due to bed rest